Acknowledgment to referees 2023 - leilamahasti jouybari (Golestan University of Medical Sciences, 2023)
The Editorial team at the Journal of Research Development in Nursing and Midwifery would like to extend our heartfelt gratitude and recognition to the reviewers who dedicated their time and expertise to review manuscripts for J Res Dev Nurs Midw in 2023. Your commitment and contributions have been invaluable in maintaining the high quality of the articles published in our journal. We express our sincerest appreciation to all the exceptional scientists, researchers, and clinicians who have served as reviewers and have been an integral part of our community. Editor-in-Chief Prof. Leila Jouybari Abdolhalim Rajabi Assistant Professor of Epidemiology, Department of Biostatistics and Epidemiology, School of Health Golestan University of Medical Sciences. Akram Sanagoo Associate Professor of Nursing, School of Nursing and Midwifery, Golestan University of Medical Sciences. Ali Asghar Jesmi Marghzar Assistant Professor of Nursing, Sabzevar University of Medical Sciences Ali Kavosi Instructor of Nursing Education, School of Nursing and Midwifery, Golestan University of Medical Sciences Ali Mohammadi Assistant Professor of Epidemiology, School of Health Military Health Research Center, Life Style Institute, Baqiyatallah University of Medical Sciences Amin Talebpour Research Center for Evidence Based Medicine (RCEBM), Tabriz University of Verified email at tbzmed.ac.ir Amrollah Sharifi Assistant Professor of Nutritional Sciences, Department of Nutritional Sciences, School of Medicine Hamadan University of Medical Sciences BiBi Hajar Zahmatkesh Assistant Professor of Reproductive Health, Department of Public Health, School of Health, Golestan University of Medical Sciences Elham Adibmoghaddam Assistant Professor of Reproductive Health, Department of Midwifery, School of Nursing and Midwifery, Golestan University of Medical Sciences Elham KHoori Associate Professor of Reproductive Health, Department of Midwifery, School of Nursing and Midwifery, Golestan University of Medical Sciences Elham Lotfalinezhad Assistant Professor of Gerontology, Department of Psychiatry and Community Health Nursing, School of Nursing and Midwifery, Golestan University of Medical Sciences Farzaneh Barati Assistant Professor of Nursing, Department of Medical Surgical Nursing, School of Nursing and Midwifery, Golestan University of Medical Sciences Fataneh GHadirian Assistant Professor of Nursing, Department of Psychiatric Nursing and Management, School of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences Fatemeh Mehravar Assistant Professor of Epidemiology, Department of Biostatistics and Epidemiology, School of Health Golestan University of Medical Sciences Fatemeh Seifi Assistant Professor of Higher Education Management, School of Nursing and Midwifery,Golestan University of Medical Sciences Fereshteh Araghian Assistant Professor of Nursing, School of Nursing and Midwifery, Mazandaran University of Medical Sciences Ghambar Roohilemraski Assistant Professor of Healthcare Services Management, School of Nursing and Midwifery Golestan University of Medical Sciences Gholam Reza Mahmoodi Shan Associate Professor of Nursing,Department of Psychiatry and Community Health Nursing, School of Nursing and Midwifery,Golestan University of Medical Sciences Hamid Asayesh Instructor of Nursing,Department of Nursing, School of Nursing,Spiritual Health Research Center,Qom University of Medical Sciences Hamid Hojjati   Assistant Professor of Nursing,Department of Psychiatry and Community Health Nursing, School of Nursing and Midwifery,Golestan University of Medical Sciences Hamideh Mancheri   Assistant Professor of Nursing Education,Department of Psychiatry and Community Health Nursing, School of Nursing and Midwifery,Golestan University of Medical Sciences Homeira Khoddam Associate Professor of Nursing, Department of Reproductive Health Midwifery, School of Nursing and Midwifery, Golestan University of Medical Sciences Katayoun Jalaliaria Instructor of Midwifery, Department of Midwifery, School of Nursing and Midwifery, Golestan University of Medical Sciences Khadijeh Yazdi Associate Professor of Nursing, Department of Medical Surgical Nursing, School of Nursing and Midwifery, Golestan University of Medical Sciences Leila Jouybari Professor of Nursing, Department of Reproductive Health Midwifery, School of Nursing and Midwifery, Golestan University of Medical Sciences Leili Borimnejad Professor of Nursing, School of Nursing and Midwifery,Nursing and midwifery care research center,Health Management Research Institute,Iran University of Medical Sciences Seyedeh Mahboobeh Rezaeean Instructor of Midwifery,Department of Midwifery, School of Nursing and Midwifery,Torbat Heydariyeh University of Medical Sciences Mahin Tatari Golestan University of Medical Sciences | GOUMS · Department of Midwifery,  Matster of Biostatistics Mahnaz Modanloo Associate Professor of Nursing, Department of Psychiatry and Community Health Nursing, School of Nursing and Midwifery, Golestan University of Medical Sciences Mahsa Besharat Assistant Professor of Pediatrics,Department of Pediatrics, School of Medicine, Golestan University of Medical Sciences Marjan Mardani Hamooleh Associate Professor of Nursing,School of Nursing and Midwifery,Nursing and midwifery care research center,Health Management Research Institute,Iran University of Medical Sciences Maryam Chehrehgosha Instructor of Nursing,Department of Operating Room, School of Allied Medical Sciences, Golestan University of Medical Sciences Masoud Mohammadi Assistant Professor of Medical Librarianship and Information Sciences,School of Allied Medical Sciences,Golestan Research Center of Gastroenterology and Hepatology, Golestan University of Medical Sciences Mohammad Taghi Badeleh Shamoushaki Assistant Professor of Health Psychology,School of Medicine,Golestan University of Medical Sciences Mohamad Ali Yadegari Assistant Professor of Nursing, Department of Operating Room and Anesthesiology, School of Nursing and Midwifery,Zanjan University of Medical Sciences Mojtaba Ghanbari Ghalesari Assistant Professor of Nursin,g Department of Nursing, School of Nursing and Midwifery, Babol University of Medical Sciences Mona Alinejad-Naeini Assistant Professor of Nursing, School of Nursing and Midwifery, Hazrat-e Ali Asghar Children's Hospital,Iran University of Medical Sciences Mousa Ghelichi-Ghojogh Assistant Professor of Epidemiology, Department of Biostatistics and Epidemiology, School of Health, Metabolic Disorders Research Center, Golestan University of Medical Sciences Narjes Sadat Borghei Associate Professor of Reproductive Health, School of Nursing and Midwifery,Golestan University of Medical Sciences Rahman Berdi Ozouni-Davaji Assistant Professor of Psychology, Department of Psychiatry, School of Medicine, Golestan University of Medical Sciences Razieh Froutan Associate Professor of Nursing, Department of Medical Surgical Nursing, School of Nursing and Midwifery, Nursing and Midwifery Care Research Center,Mashhad University of Medical Sciences Samira Foji Assistant Professor of Nursing, Sabzevar University of Medical Sciences Sedigheh Moghasemi Assistant Professor of Reproductive Health, School of Nursing and Midwifery, Golestan University of Medical Sciences Shohreh Kolagari Associate Professor of Nursing, Department of Medical Surgical Nursing, School of Nursing and Midwifery, Golestan University of Medical Sciences Somayeh Ghorbani Assistant Professor of Biostatistics, Rheumatology Research Cente,r Golestan University of Medical Sciences Tayebe Ziaei Associate Professor of Reproductive Health, School of Nursing and Midwifery, Golestan University of Medical Sciences Zahra Sabzi Associate Professor of Nursing, Department of Reproductive Health Midwifery, School of Nursing and Midwifery, Golestan University of Medical Sciences